2012
DOI: 10.1007/s11104-012-1363-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rhizodeposition at field scale: upscaling of a 14C labeling study

Abstract: Background and aims Rhizodeposition of plants is the most uncertain component of the carbon (C) cycle. By existing approaches the amount of rhizodeposition can only roughly be estimated since its persistence in soil is very short compared to other organic C pools. We suggest an approach to quantify rhizodeposition at the field scale by assuming a constant ratio between rhizodeposited-C to root-C. Methods Maize plants were pulse-labeled with 14 CO 2 under controlled conditions and the soil 14 CO 2 efflux was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 51 publications
4
65
1
Order By: Relevance
“…In contrast, strong correlations between total rhizodeposited 13 C and leaf or root biomass were observed supporting previous studies which assume that exudation patterns were affected by species identity and particularly root biomass (Van der Krift et al 2001;Blagodatskaya et al 2014). All together, these results suggest that changes of rhizodeposition rate following fertilization were not dependent of soil microbial community but rather support a substantial influence of plant features (Farrar et al, 2003;Warembourg et al, 2003;Kuzyakov and Cheng, 2004;Badri and Vivanco, 2009) on rhizodeposition processes as already demonstrated by previous studies on grassland (Van der Krift et al, 2001;Pausch et al, 2013) and forest species (Bowden et al, 2004). …”
Section: Discussionsupporting
confidence: 89%
“…In contrast, strong correlations between total rhizodeposited 13 C and leaf or root biomass were observed supporting previous studies which assume that exudation patterns were affected by species identity and particularly root biomass (Van der Krift et al 2001;Blagodatskaya et al 2014). All together, these results suggest that changes of rhizodeposition rate following fertilization were not dependent of soil microbial community but rather support a substantial influence of plant features (Farrar et al, 2003;Warembourg et al, 2003;Kuzyakov and Cheng, 2004;Badri and Vivanco, 2009) on rhizodeposition processes as already demonstrated by previous studies on grassland (Van der Krift et al, 2001;Pausch et al, 2013) and forest species (Bowden et al, 2004). …”
Section: Discussionsupporting
confidence: 89%
“…No variation in soil organic C associated with grapevine trees was observed within the vineyards. The high TOC observed in soil under oak canopies might be the result of the long-term transfer to the soil of high amounts of organic C deriving from the aboveground tree biomass (Moreno et al, 2007) and tree rhizodeposition (Pausch et al, 2013), as well as from dejections of grazing sheep that, particularly in the summer, rest in the shade under the tree canopies. According to what was observed by Gómez-Rey et al (2012), PAU showed a content of C 0 , MR basal , and MR higher than that in PAO, indicating a larger soil microbial activity and a positive trend for C stock potential.…”
Section: Discussionmentioning
confidence: 99%
“…This translates to 4.6 t C ha −1 translocated belowground annually, which is partitioned into 2.1 t C ha −1 lost as CO 2 by rhizosphere respiration, 2.2 t C ha −1 allocated to root biomass and 0.3 t C ha −1 incorporated into SOC. However, the longevity of the latter maize-C pool in soil post-27 days remains to be determined, including the potential positive priming effect of maize rhizoexudation on extant SOC (Pausch et al 2012).…”
Section: Discussionmentioning
confidence: 99%